P065: Out-of-hospital cardiac arrest patients eligible for extracorporeal cardiopulmonary resuscitation in Regina emergency departments. (May 2020) - Lee, B.; Sy, E.; Clay, A.
Abstract : Introduction: Extracorporeal cardiopulmonary resuscitation (ECPR) is a rapidly evolving technology for clinical use in patients with refractory cardiogenic arrest. Out-of-hospital cardiac arrest (OHCA) is a common cause of unexpected death and has a low survival rate. There is increasing evidence that suggests better outcomes for (OHCA) patients, including improved neurological outcomes and survival rates, who are started on extracorporeal corporeal membrane oxygenation (ECMO) versus traditional resuscitation methods. Methods: We conducted a retrospective chart review of 200 out-of-hospital cardiac arrest patients presenting to Regina emergency departments from January 1, 2017 to March 31, 2019. Eligibility for ECPR was assessed using different clinical criteria from different ECPR programs (University of British Columbia, University of Michigan, and a hypothetical "Regina" criteria created for this study). Outcomes of the eligible patients were compared using descriptive statistics with SPSS version 22. Results: Between four different criteria, 15%, 9.5%, 7.5%, and 3.5% of patients were respectively eligible to receive ECPR. Of patients who met eligibility for all four criteria, 80% were male, the average age was 61 years old, the average Cerebral Performance score was 4.46, and 83% died in hospital. There was a low survival rate of eligible patients, with rates of 16%, 17%, 20%, and 28% in each group. The survival rate for all patients was 21% and the average CPC score was 4.35. Conclusion: The significant percentage of patients were eligible for ECPR upon presentation to Regina Emergency Departments. Patients who were eligible had low survival rates and poor neurological outcomes, suggesting that ECPR could prove to be a valuable clinical tool that could improve patient outcomes in Saskatchewan. There were considerable differences in patient eligibility percentages based on different criterion. Differences in inclusion/exclusion criteria, modifying the expected annual number of ECPR eligible OHCA patients, could provide valuable information on required resources and planning for implementation of an ECPR program in a smaller centre, such as Regina.